The host-searching behaviour of coccophagus atratus compere (Aphalinidae: hymenoptera) - Clark, Maxwell Maitland (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1985)
The host-searching behaviour of the parasitoid Coccophagus atratus Compere was investigated. C. atratus parasitoids have unusual host relationships. Female offspring develop in scale insects but male offspring develop hyperparasitically on their conspecific females, or on other parasitoid species. C. atratus females, therefore, must locate, identify and oviposit into two different types of hosts. A primary aim of this thesis, was to identify when and how the behaviour of a female, searching for hosts suitable for female offspring, differed from that of a female searching for hosts suitable for male offspring. This was done by investigating and comparing the behaviour of virgin and mated females. Virgin females can lay only male eggs while mated females can lay both male and female eggs. The role of plant odours and host odours in attracting C. atratus females to the host habitat and to their scale insect hosts was examined with the aid of an olfactometer. Field observations, to test the validity of results obtained in laboratory experiments, indicated that C. atratus females do not search initially for for their hosts' food plants, but search directly for hosts. Only when hosts were physically located did the behaviour of virgin and mated females differ. Recognition cues used by the females to distinguish between the two types of hosts were identified. Finally, the implications of results obtained were discussed in relation to ecological and evolutionary aspects of heteronomous parasitoid biology.
Keywords: Coccophagus; Hymenoptera; Insects -- Host plants; Insect-plant relationships